Comparison of Reproductive Performance of Domesticated Litopenaeus vannamei Females Reared in Recirculating Tanks and Earthen Ponds: An Evaluation of Reproductive Quality of Spawns in Relation to Female Body Size and Spawning Order - Ren, Shengjie; Mather, Peter B.; Tang, Binguo; Hurwood, David A. (Frontiers in Marine Science, 2020)
Optimizing broodstock reproductive performance quality in aquaculture is crucial for planning long-term genetic improvement programs to facilitate the development of an effective seed dissemination strategy. In the current study, we investigated the relative reproductive performance of female Litopenaeus vannamei broodstock reared under two common rearing systems: (i) recirculating tanks (RT) and (ii) earthen ponds (EP), and evaluated relative individual female reproductive performance (RT vs EP), quality of reproductive females in relation to individual body size of spawners, and female reproductive quality relative to spawning order (number of spawning events per individual). No significant difference (P > 0.05) was observed between RT-reared vs EP-reared females for: (i) number of eggs per spawn (RT = 23.34 ± 0.72 × 104, EP = 22.45 ± 0.67 × 104), (ii) number of nauplii per spawn (RT = 19.85 ± 0.85 × 104, EP = 19.53 ± 0.83 × 104), (iii) hatch rate of eggs per spawn (RT = 0.83 ± 0.02, EP = 0.85 ± 0.02), or (iv) relative fecundity – number of eggs per gram of female (RT = 5.51 ± 0.15 × 103, EP = 5.78 ± 0.19 × 103). We recorded 136 and 101 spawning events for RT and ER females, respectively. EP-reared females (1.93 ± 0.23) showed a significantly higher (P < 0.01) spawn frequency compared with RT-reared females (1.34 ± 0.12). Females under the two treatments showed a similar pattern for body size with larger body size spawners producing higher (P < 0.01) numbers of eggs and nauplii per spawn than smaller spawning females. Of interest, we observed that while large-sized RT-reared females recorded a higher mean spawn frequency, medium-sized females from the EP treatment showed double the spawn frequency compared with small or large sized females of EP. No compromise was evident in the quality of individual female reproductive performance for multiple spawning individuals compared with first or second spawning order events for all reproductive parameters evaluated (P > 0.05). The data generated here will be used to optimize a genetic breeding strategy for our broodstock line and to develop a seed distribution strategy for the local production sector in China.